How to narrate a forest? Imbrications between arts and sciences on Isla Victoria - Klier, Gabriela; Gattás Vargas, Maia (Bosque (Valdivia), 2022)
The purpose of this manuscript is to contribute to the discussion on the links between arts and sciences in the practices of environmental care and biodiversity conservation. The starting point is the experience in Isla Victoria Laboratory project. This island, located in Nahuel Huapi Lake, is a historical environmental emblem, where a century ago the most important Arboretum in Patagonia was installed and where many conservation projects are currently being developed. The study presents a debate of de arts-sciences relationship in the context of environmental crisis, and hence, taking the case of Isla Victoria as a starting point, explores certain questions and experiences on the horizons of these approaches in pursuit of environmental care.